BUDAYA LINGKUNGAN DAN NORMA SEBAGAI FAKTOR PENENTU PERILAKU KONSUMEN TERHADAP PRODUK BERWAWASAN LINGKUNGAN - Ignatius Heruwasto (Journal of Management and Business, 2012)
The characteristic of green product is different compare to conventional product, and makes a gap on the theory to explain attitude and behavior toward green product. The objective of this article to find the determinant factors of consumer behavior toward green product. This article uses the theories from consumer behavior and marketing literature to construct an integrative and comprehensive nomological model, to explain the determinant factors influence the attitude and behavior on green product. This article includes a new value concept, the green values, and with the norms become an important factor that influence perceived customer value, attitude and behavior on green product. The article points out that the green culture is the key determinant factor to increase the use of green product, and the green culture should be cultivated to prevent the environment degradation from the consumption of conventional product.